Subthalamic Deep Brain Stimulation in Parkinson's Disease: A Boon or Bane – A Single Centre Retrospective Observational Study from India - Hazra, Darpanarayan; Chandy, Gina Maryann; Ghosh, Amit (Asian Journal of Neurosurgery, 2023)
Background Subthalamic deep brain stimulation (STN-DBS) for refractory Parkinson's disease (PD) is more of a modality of treatment that is empirical, for which a physiological explanation is being sought. This study was done to determine the outcome and complications of patients undergoing STN-DBS for PD.Methods This retrospective observational cohort study was conducted in an advanced neuromedicine facility in eastern India for 9 years (August 2013–August 2022), which included all patients undergoing STN-DBS.Results A total of 53 patients were operated on during the study period. The mean age group of the study population was 60.5 (standard deviation [SD]: 8.2) years with a male (33 [62.3%]) predominance. The most common presenting complaints included rigidity and hypokinesia (27), severe dyskinesia (21), and tremors (17). During the postoperative period, rigidity and hypokinesia (21), severe dyskinesia (16), and tremors (12) improved significantly in a subset of the patients. The majority (45 [84.9%]) of these cases received bilateral monopolar simulation, whereas three patients (5.7%) had bilateral bipolar stimulation. Unilateral bipolar stimulation was used in five (9.4%) patients. In the immediate postoperative period, they were initiated on limb, speech, and swallowing therapy as indicated. Surgery-related complications were seen in five (9.4%) cases. At 6 months of follow-up, a significant improvement in the Unified PD rating scale component (mainly motor examination and complication of PD therapy) was noted in the majority (36 [67.9%]) of patients. One patient developed neuroleptic malignant syndrome and succumbed to his illness on the fourth postoperative day.Conclusion Given these findings, STN-DBS appears to be a good, safe, and effective treatment for a subset of medically refractory PD with an overall improvement in two-thirds of the study cohort and less than 10% risk of complications.
Keywords: Parkinson's disease; deep brain stimulation; subthalamic deep brain stimulation; movement disorder